"A Study on Health Management Information System (HMIS) with reference to Periyanaickenpalayam Government Hospital, Coimbatore" - Murugan, Saravanapriya (Journal of Contemporary Research in Management (JCRM), 2017)
The Government of Tamil Nadu has overcome the hurdles in patient care at Government Hospitals by implementing Health Management Information System (HMIS). HMIS is a combination of Information Technology (IT) and Health Care Management. To improve health care management in the State, the only solution is to introduce Information and Communication Technology (ICT) in health care management system. The present HMIS is an initiative of Government of Tamil Nadu through Tamil Nadu Health Systems Project (TNHSP). In this paper, Periyanaickenpalayam Government Hospital (GH) is taken for observation and data collection. The primary objective of this study is to understand the working process and modules of Hospital Management System (HMS) and how it is linked with HMIS. The secondary objective of this study is to understand the services rendered by the health workers to the public though HMS and HMIS. For detail description, real time photos and real time data are captured and used as figures and screenshots. The primary and secondary sources of data are published with prior permission from hierarchical authorities from TNHSP.